Assessing Effectiveness of anaerobic threshold and respiratory compensation point on fat and carbohydrate oxidations during exercise in sedentary males: Anaerobic Threshold and Substrate Oxidation - Ugras, Seda; Algul, Sermin; Ozcelik, Oguz (Progress in Nutrition, 2021)
Study Objectives: Anaerobic threshold (AT) and respiratory compensation point (RCP) are two important metabolic set points. We aimed to determine effects of exercise intensity at AT and RCP on the balance of substrate oxidation rates. Methods: Eleven male participants performed an incremental exercise test to exhaustion on a cycle ergometer to estimate AT and RCP. Subsequently, we conducted three 30 minute constant load exercise tests at AT (WAT), RCP (WRCP) and 25% below AT (W